Pendidikan Wahdatul ‘Ulum dalam Al-Qur’an - Indah Widya Jaya Putri Nasution; Tasya Amelia Putri Siregar; Asnil Aidah Ritonga; Mohammad Al Farabi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The aim of wahdatul 'ulum-based education is to create a comprehensive knowledge system. There are problems that have existed for a long time regarding science being based on general knowledge and science being based on religion. And many Islamic communities still hold the view that religion and Islam cannot coexist because they have different domains. Therefore, wahdatul 'ulum-based education emerged to unite the unity of knowledge. This research uses the library research method and the tahlili interpretation method. The conclusion of this research is that in the Al-Qur'an the verses that talk about wahdatul 'ulum are found in surah Al-A'raf; 172-173, Al-Imran; 190-191, Al-Ahqaf; 23, Al-Mulk; 26 where these verses illustrate that wahdatul 'ulum-based education is very important to implement and what makes ulul albab special.